2012
DOI: 10.1175/jtech-d-11-00163.1
|View full text |Cite
|
Sign up to set email alerts
|

The Informational Value of Pressure-Based Single-Station Proxies for Storm Activity

Abstract: Air pressure readings and their variations are commonly used to make inferences about storm activity. More precisely, it is assumed that the variation of annual and seasonal statistics of several pressure-based proxies describes changes in the past storm climate qualitatively, an assumption that has yet to be proven.A systematic evaluation of the informational content of five pressure-based proxies for storm activity based on single-station observations of air pressure is presented. The number of deep lows, lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 25 publications
2
11
0
Order By: Relevance
“…4.9, the PC1 over all eight indices captures the calm period of the 1960s and 1970s indicating that it is better to use a number of different indices rather than relying on only one. The highest correlation between HiResAFF annual extreme wind speeds and singlestation proxies was achieved for the pressure tendency over 8 h (r = 0.50) confirming the work of Krueger and von Storch (2012). Remarkably high values for the 8-h pressure tendencies on the one hand and very low values for the number of deep lows on the other hand indicate low confidence in the data before around 1850 probably due to irregular pressure readings.…”
Section: Long-term Wind Climatesupporting
confidence: 62%
See 1 more Smart Citation
“…4.9, the PC1 over all eight indices captures the calm period of the 1960s and 1970s indicating that it is better to use a number of different indices rather than relying on only one. The highest correlation between HiResAFF annual extreme wind speeds and singlestation proxies was achieved for the pressure tendency over 8 h (r = 0.50) confirming the work of Krueger and von Storch (2012). Remarkably high values for the 8-h pressure tendencies on the one hand and very low values for the number of deep lows on the other hand indicate low confidence in the data before around 1850 probably due to irregular pressure readings.…”
Section: Long-term Wind Climatesupporting
confidence: 62%
“…Hanna et al (2008) found similar results based on a daily pressure variability index calculated as absolute 24 h pressure differences, that is Dp = |p t+24 − p t+0 |, for the British Isles since 1830 and for Denmark since 1874 confirming increased storminess at the end of the nineteenth century and the 1980s to 1990s, with the 1880s being the stormiest decade. The informational value of five different pressure-based storminess indices including those used by Bärring and von Storch (2004) and Hanna et al (2008) was evaluated by Krueger and von Storch (2012). The authors confirmed the general usefulness of the indices as storminess proxies, with absolute pressure tendencies per six or eight hours containing the highest informational value.…”
Section: Long-term Wind Climatementioning
confidence: 81%
“…More recent climatologies of synoptic storm tracks rely on pressure data derived from numerical model reanalyses (Thomas and Martin 2007;Nieto Ferreira et al 2013). Pressure tendency (i.e., the change in pressure over a specified duration) has been used frequently to identify preferred geographical locations for cyclogenesis and anticyclogenesis (Sanders and Gyakum 1980;Krueger and von Storch 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Even single-station pressure indices such as strong pressure changes over 6-or 24-h periods or the annual number of deep lows provide useful information about long-term variations in the wind and storm climate (Krueger and von Storch 2011). The information content to describe long-term variations in the statistics of pressure and wind is even higher for indices of geostrophic wind speeds calculated from triangles of daily pressure observations (Krueger and von Storch 2012). The correlation of geostrophic wind speeds calculated from station triplets with real model wind speeds is especially high over open terrain and sea areas (i.e.…”
Section: Regional Variations In Pressure and Wind Since Around 1800mentioning
confidence: 99%